Tense and mood in persian and English: A contrastive and error analyses / Nezam Emadi - Nezam, Emadi (2013)

(untitled)
The present study investigates the two grammatical categories of tense and mood in Persian and English through the contrastive analysis (CA) and error analysis (EA) approaches. The present study seeks to provide a practical and descriptive structural grammar in terms of tense and mood and to identify the areas of difficulty encountered by Persian EFL learners as well. The verb is one of the main parts of speech in a language and the correct use of tense has an important role in language learning and communication in the tense languages like English and Persian. In the CA, the verbal forms and their applications in both English and Persian are described and then they are juxtaposed in order to find out the similarities and differences between them in terms of their tenses and moods. Furthermore, in the EA, the errors made in a structural test consisting of one hundred items of all English tenses which was administered to sixty Iranian undergraduate students of Shiraz University in Iran were analyzed. Through this EA approach, the frequency of occurrence of the errors and the sources of the errors were analyzed. The conclusions and recommendations are made based on the findings of the two approaches of CA and EA and from the two surveys comprising a questionnaire and interviews from 30 English teachers from 10 universities in Iran. According to this reseach, the number of tenses and moods are the same in both languages. There are twelve tenses in English and Persian while there is no often one to one correspondence in the form and use of them. In addition, there are three moods in both languages including Indicative, Subjunctive and Imperative. Notwistanding, the subjunctive mood in Persian has been already grammaticalized while in modern English it has declined even though we can say it is still alive. iv The pedagogical implications can help students and teachers in the learning and teaching processes of the target language. The EA results showed that negative interlingual transfers caused many errors by the participants in the test and on the other hand, many other errors were caused by intralingual errors of ‘ignorance of rule restrictions’ or of ‘false concepts hypothesized’. This will affirm the view that the native or non-native English teachers should have sufficient knowledge of the two languages - Persian as the source/first language and English as the target/foreign language. It is strongly recommendation that teachers give enough information to the EFL learners by illustrating some examples concerning the notions of stative verbs, dynamic verbs, achievement verbs, durative verbs, punctual or instantaneous verbs, perfective and progressive aspects in English language. Furthermore, regarding the English teachers’ attitudes and experience, and despite the shortage of time for English lessons which is claimed by the almost all teachers,the communication strategies needed for foreign language pattern learning should also not be ignored.